Detection of Weakly Expressed Trypanosoma cruzi Membrane Proteins Using High‐Performance Probes. (30th March 2018) - Cruz‐Bustos, Teresa; Moreno, Silvia N.J.; Docampo, Roberto
Abstract: Membrane proteins in trypanosomatids are, in general, weakly expressed and confirmation of their subcellular localization frequently requires their overexpression with epitope tags. However, overexpression can lead to mislocalization of the probes. Viswanathan et al. ( Nat. Methods, 2015, 12:568) described high performance tags for localization of weakly expressed proteins. We report here the use of these protein tags, named "spaghetti monster, " for CRISPR/Cas9‐mediated C‐terminal endogenous tagging of Trypanosoma cruzi to localize two weakly expressed transient receptor potential channels to acidic compartments. The results indicate that this method will improve the detection of membrane proteins in T. cruzi .